MIGREN: PATOMEKANISME, DIAGNOSIS, DAN PENATALAKSANAAN - Aprilia E. J. Tuda; Natanael Ritung; Arthur H. P. Mawuntu (Jurnal Sinaps, 2020)
Migraine is a neurovascular headache disorder, which often causes disability, recurrent, and some are hereditary. This condition manifests as headache, hypersensitivity to visual, auditory, olfactory, or somatosensory stimuli, and also nausea and vomiting. Migraine has a complex process but is related to the activation of the trigeminovascular system. The classification of migraine based on International Classification of Headache Disorder version 3 (ICHD-3) consists of migraine without aura, migraine with aura, chronic migraine, complicated migraine, probable migraine, and episodic syndromes that may be associated with migraine. The management has a multifactorial nature. We will further discuss the patho-mechanism, diagnostic criteria, and management of migraine.